Perspectiva teórica acerca de la práctica del judo, como método para la educación en valores del practicante - Moncada Cok, Walter Enrique (2023)
The present covers a study about the incidence of judo as a method aimed at the development of education in values. For its development, we select a method from the theoretical level and the empirical level of scientific research, the first to analyze the results derived from the application of empirical methods, through which we collect the information required to comply with the programmed work objectives. Among the main findings found in the research developed is a diagnosis of the existing situation in the province under study, as well as a system of actions aimed at facilitating the practitioner's education in values. Reaching conclusions that taking into account by the relevant authorities could contribute to the formation of a better citizen, capable of contributing more to Ecuadorian society, being endowed with useful values for the practice of sport and for life in general, falling In the above, the significance, import and feasibility of this final thesis report.